2017
DOI: 10.5502/ijw.v7i1.540
|View full text |Cite
|
Sign up to set email alerts
|

Labor earnings reductions, happiness levels and needs hierarchy

Abstract: One of the main economic outcomes of the recent Great Recession has been the decrease of labor earnings in many countries. The relevant literature indicates that earnings and other socioeconomic predictors can influence levels of happiness. This paper tests the effect of pay cuts on happiness levels based on the psychological model of hierarchical needs. The basic idea of hierarchy is that the most important needs must be satisfied first before the secondary needs come into the picture. In a happiness research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…According to Lam (2016), a substantial amount of low-income households' expenditure goes towards essential needs, such as shelter and food, whereas high-income households typically spend more on needless items. This is corroborated by Drakopoulos and Grimani (2013), who found that the satisfying of non-basic requirements becomes essential at higher income levels, whereas a large amount of the income is spent on food at low-income levels, since food is a basic need. The cost of living is proportional to wages and represents the amount of money required to cover fundamental living expenses.…”
Section: Literature Reviewmentioning
confidence: 67%
“…According to Lam (2016), a substantial amount of low-income households' expenditure goes towards essential needs, such as shelter and food, whereas high-income households typically spend more on needless items. This is corroborated by Drakopoulos and Grimani (2013), who found that the satisfying of non-basic requirements becomes essential at higher income levels, whereas a large amount of the income is spent on food at low-income levels, since food is a basic need. The cost of living is proportional to wages and represents the amount of money required to cover fundamental living expenses.…”
Section: Literature Reviewmentioning
confidence: 67%
“…In addition, recent relevant studies such as Diener et al . (2013) and Drakopoulos and Grimani (2017) have converged on the perception that the degree of impact which a change in income has on Subjective Well-Being is related to the prioritization of the satisfaction of the each employee's needs and to the extent that prosperity is perceived by the individual as more material or related to intrinsic values and motivations, such as recognition. The latter is confirmed by the findings of the present study, which identified recognition and the level of autonomy as important factors for a positive contribution to the job satisfaction of doctors in public Greek hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In Economics, it may be easier to estimate the severity of poverty and effect of an increase in income. To this effect, it is easier to estimate the income effect of (increased) motivation (see Benda-Prokeinová et al, 2017; Drakopoulos & Grimani, 2017; Frey, 1997; Xiao & Anderson, 1997). There are few of such studies on indigent graduate students who seek to acquire a higher degree in Education.…”
Section: Motivation To Acquire Higher Degree In Education: a Methodological Reviewmentioning
confidence: 99%
“…Other economic theories of motivation are concerned with general consumer utility maximization (see Benda-Prokeinová et al, 2017, for their estimation of Engel curve and consumer behavior). Seely (1992) earlier attempted to fit budget constraint to a utility maximization model to indicate the level of motivation while Drakopoulos and Grimani (2017) fitted data to estimate happiness levels of individuals (motivation) when their income is reduced. But literature that estimates the income effect for acquiring higher degree in Education is rare.…”
mentioning
confidence: 99%